6000=(40+x)+(40+x)+x+x

Simple and best practice solution for 6000=(40+x)+(40+x)+x+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6000=(40+x)+(40+x)+x+x equation:


Simplifying
6000 = (40 + x) + (40 + x) + x + x

Remove parenthesis around (40 + x)
6000 = 40 + x + (40 + x) + x + x

Remove parenthesis around (40 + x)
6000 = 40 + x + 40 + x + x + x

Reorder the terms:
6000 = 40 + 40 + x + x + x + x

Combine like terms: 40 + 40 = 80
6000 = 80 + x + x + x + x

Combine like terms: x + x = 2x
6000 = 80 + 2x + x + x

Combine like terms: 2x + x = 3x
6000 = 80 + 3x + x

Combine like terms: 3x + x = 4x
6000 = 80 + 4x

Solving
6000 = 80 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
6000 + -4x = 80 + 4x + -4x

Combine like terms: 4x + -4x = 0
6000 + -4x = 80 + 0
6000 + -4x = 80

Add '-6000' to each side of the equation.
6000 + -6000 + -4x = 80 + -6000

Combine like terms: 6000 + -6000 = 0
0 + -4x = 80 + -6000
-4x = 80 + -6000

Combine like terms: 80 + -6000 = -5920
-4x = -5920

Divide each side by '-4'.
x = 1480

Simplifying
x = 1480

See similar equations:

| 18b^2+25b-3= | | 10=2(u-5)-6u | | 1474x+4=20 | | 6000=(40+x)(x) | | 0.2(x+60)-0.08(x-30)=8.4 | | 12x+6=8x+42 | | 1/6x-2/7=4/7 | | f(x)=x^2+7x-7 | | (2x+1)(9x+b)=6x^2-5x+c | | 7.93-15.29v=0.66v | | 77=.5(7)(9+b) | | 6000=40w+w^2 | | 2(2c-3)-7=2c+5 | | a/4=32 | | 9x+1.5=19.5 | | -5w+4w^2+9=0 | | 6a-4ifa=7 | | 30-15x+6x=32+16 | | 4x+31=-x+1 | | 4-11=3 | | (4x^2-32x-26)/(x-9) | | 2=-3d+14 | | 3+8x=-3(-1-7x) | | -15=c/9-10 | | k=25+10x | | (7-z)(3z-8)=0 | | 48x^2-x-15=0 | | 2(x+4)+6=50 | | -5(-3p+3)=8(6p-6) | | (3x-7)(4x+4)=0 | | 0.3=x(1+x) | | 88=2(6p+8) |

Equations solver categories